Experimental researches fire resistance of polymer composite structures with fire protection - Kudryashov Вадим; Polevoda Иван; Drobysh Антон; Solov’yanchik Андрей (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2015)
On the basis of the research developed an experimental model of composite structure, provides the required fire resistance of composite materials for use as building elements of any degree of fire resistance developed recommendations for the use of polymeric composite materials reinforced with glass fibers, based on isophthalic resin, based on their fire resistance in accordance with the test report.